CHEMICAL EVOLUTION IN ALGOLS - Glazunova, L. V. (Одеські астрономічні публікації, 2012)
We discuss the chemical abundance in Algol-type systems produced by different authors. Till this time most evolutionary changes in the chemical abundance of the components of Algols were studied by carbon depletion. We obtained the following results: 1) detections of carbon abundance in the atmosphere of donor were reported in two articles, but them don't show dependence from the mass ratio and the mass donor, 2) the carbon abundance in the atmosphere accretor for the same system in research different authors is very different, also it isn't dependency from the ratio of the masses and the masses of accretor. Summary: while were observed evolutionary changes in the carbon abundance for Algol's component, but a precision was low and studied the small number of systems and can not linke to the carbon abundance and mass ratio and also the masses of the components - the basic parameters of the binary system evolution.